Biological activities of methanolic extract of selected local mushrooms - Hashim, Mahfuzatunajla (2012)
Local selected mushrooms; Ganoderma boninense, Auricularia auricula judae,Pleurotus cystidiosus and one new unidentified (BS01) were evaluated for the antioxidant, antimicrobial, anti-tyrosinase, anti-hyaluronidase, anti-inflammatory and insulin secretion activities. The antioxidant activity was measured using the DPPH (1,1-diphenyl-2-picryl hydrazyl) radical scavenging activity assay and ferric reducing antioxidant power assay (FRAP). In antioxidant activity, both G.boninense and A. A. judae showed the highest activity for DPPH and FRAP assays with the lowest IC50 value. The IC50 of G. boninense and A. A. judae for DPPH were 129.8 ± 1.8 and 198.5 ± 1.5 while for FRAP were 25.8 ± 5.0 and 52.7 ± 3.8,respectively. Anti-inflammatory activity was determined by inhibition of nitric oxide (NO) and measuring the nitrite (NO2 -) formation using Griess assay. However, only G. boninense showed inhibitory effect of NO inhibition with IC50 value at 151.3 μg/mL but the extract was also toxic to the RAW 264.7 cell at 500 μg/mL with cell viability percentage of 39.28 ± 2.5% only. Tyrosinase inhibitory was determined by a spectrophotometric method using L-3,4-ihydroxyphenylalanine (L-DOPA) as a substrate. BS01 exhibited significant (p < 0.05) inhibition with the IC50 value at 279.4 μg/mL and G. boninese at 474.4 μg/mL. The colorimetric Morgan-Elson method was carried out for hyaluronidase assay but all of the mushrooms were tested negative. Insulin secretion activity was measured using rat pancreatic β-cell line, BRIN-BD11 cells and the insulin level produced by the cell line was measured by an enzyme-linked immunosorbent assay using a commercial rat insulin ELISA. Among the mushrooms, G. boninense and P.cystidiosus extracts showed significant (p < 0.05) increased in insulin secretion at the concentration of 62.5, 125, 250 and 500 μg/mL. Overall, from the four mushrooms tested, G. boninense seem to exhibit more bioactive compounds and the further work could be done on the isolation, characterization and purification of the active compounds from the crude extract.